MORPHOLOGICAL ANALYSIS OF STUDENTS’ AFFIX PATTERNS IN WRITING - Ika Lusi Kristanti (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2016)
Affixation is a process that must be considered students in changing the form of words or word class. For example in changing an adjective into a noun, students must understand about the type of affixes used. For example, the word "happy" (adjective) can be changed into a noun by adding affix "-ness". So that the word changed to "happiness". In addition, students also have to pay attention to the selection of appropriate affix in writing an essay. Because the accuracy of the affix selection also influences the quality of students’ writing. Principally, the use of affix in an essay is closely related with the function of affix itself. Because the use of affix assists us in changing the form of a word as desired. This phenomenon encourages researcher to dig deeper into affixation in an essaythat’s written by student. This study emphasizes on how the process of using affix in an essay. This study is descriptive qualitative research. Source of the data is students’ writing. It is derived from students’ writing about their experiences. Meanwhile, data of this study are words that consist of affixand root. While the process of data analysis uses Fromkin et. All’s theory (2013:65) and Stockwell and Minkova’s theory (2001: 64). Based on the findings, students use two types of affix patterns, a) derivational affix, b) inflectional affix. In addition, based on the function, the students use the affixpatterns to: a) derive new word or create a new word by changing different grammatical category and b) make grammatical changes to words or make different grammatical function of words